2017
DOI: 10.1115/1.4036640
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size Distribution on Powder Packing and Sintering in Binder Jetting Additive Manufacturing of Metals

Abstract: The binder jetting additive manufacturing (AM) process provides an economical and scalable means of fabricating complex parts from a wide variety of materials. While it is often used to fabricate metal parts, it is typically challenging to fabricate full density parts without large degree of sintering shrinkage. This can be attributed to the inherently low green density and the constraint on powder particle size imposed by challenges in recoating fine powders. To address this issue, the authors explored the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(113 citation statements)
references
References 14 publications
1
92
1
2
Order By: Relevance
“…Therefore, it can be concluded that the quality of the final parts produced by BJ-AM technology is determined not only by the parameters related to green part fabrication process but also by the post-printing processes and affecting factors [14]. There exist multiple factors that could potentially influence the feature resolution and quality of the green components fabricated via BJ-AM process such as binder and powder physical properties, powder bed characteristics, droplet impact velocity, and powder material wettability to the liquid binder [13,95,155,157,158]. One of the key parameters in determining the minimum feature size and final part quality in BJ-AM process is the interactions between the liquid binder droplets and the powder materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be concluded that the quality of the final parts produced by BJ-AM technology is determined not only by the parameters related to green part fabrication process but also by the post-printing processes and affecting factors [14]. There exist multiple factors that could potentially influence the feature resolution and quality of the green components fabricated via BJ-AM process such as binder and powder physical properties, powder bed characteristics, droplet impact velocity, and powder material wettability to the liquid binder [13,95,155,157,158]. One of the key parameters in determining the minimum feature size and final part quality in BJ-AM process is the interactions between the liquid binder droplets and the powder materials.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of particle size distribution on the surface finish of additively manufactured parts has been demonstrated by different researchers in the literature [157,163]. Generally, smaller particles result in improved surface quality of components due to the diminished staircase effect, as well as the use of thinner layers [157,164].…”
Section: Resultsmentioning
confidence: 99%
“…Particle size distribution was demonstrated to have a considerable impact on the green body density of 3D-printed materials [21,25]. Multimodal particle size was shown to increase the density of BJT-printed ceramic and metallic parts.…”
Section: Particle Size Distributionmentioning
confidence: 97%
“…The main limitation of metal binder jetting is the relative density of metal parts (95-97%), which can be compared with a typical density of > 99% with laser-based powder bed systems. A number of research works have been conducted to investigate the effect of process parameters (such as layer thickness, binder saturation, drying after printing each layer) and part orientation [58,71], powder particle size and distribution [53,[72][73][74], and post-processing [47] on density, and mechanical properties. The influence of layer thickness, powder particle size and sintering profiles in the binder jetting of IN718 superalloy was studies by Turker et al [58].…”
Section: Binder Jettingmentioning
confidence: 99%